1970
DOI: 10.1111/j.1365-2818.1970.tb02252.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of stereologic methods to stratified gingival epithelia*

Abstract: SUMMARY Stereologic point‐counting procedures were applied to estimate quantitative tissue and cytoplasm parameters of the oral and the junctional epithelium of the human gingiva. Three gingival biopsies of female children, obtained and processed under standardized conditions, served (1) to determine the minimal sample size of cytoplasmic area required for estimating representative volumetric parameters in different strata of both epithelia, and (2) to compare average volume and surface density data derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1971
1971
1995
1995

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The principle of progtessive mean plots (Burn et al 1968, Schroeder & Munzel-Pedrazzoli 1970 was used to determine the minimum number of micrographs required to provide stable mean values for statistical comparisons. The sample used in this investigation provided a stable mean within the 5% (±2.5%) range.…”
Section: Materials Andmentioning
confidence: 99%
“…The principle of progtessive mean plots (Burn et al 1968, Schroeder & Munzel-Pedrazzoli 1970 was used to determine the minimum number of micrographs required to provide stable mean values for statistical comparisons. The sample used in this investigation provided a stable mean within the 5% (±2.5%) range.…”
Section: Materials Andmentioning
confidence: 99%
“…If a morphometric analysis were to be done on equatorial profiles only, it would obviously introduce a definite sampling bias in favour of the nucleus, and possibly affect the recorded volumetric parameters of subcellular components polarized with respect to the nucleus. However, Schroeder & Miinzel-Pedrazzoli (1970) have recently demonstrated that a biased sampling procedure can produce acceptable morphometric information, at least in a structurally oriented tissue (gingival epithelium).…”
mentioning
confidence: 99%
“…Indeed, these cells increase with the duration of the ulcer, as is also seen in recurrent oral ulcers (Graykowski et al, 1966;Lehner, 1969). The number of X-lymphocytes which resemble plasmablasts (Schroeder & Graf-de Beer, 1976) reached 2-2",, in one of the 3-day biopsies, suggesting that plasma cells might be generated at a later stage of ulceration. A moderate percentage of ncutrophils was found in the four biopsies and the proportion of these cells would have been greater if the central ulcerated zone had been examined.…”
Section: Discussionmentioning
confidence: 73%